Patient Age Is Significantly Related to Distant Metastasis of Papillary Thyroid Microcarcinoma - Huang, Hui; Xu, Siyuan; Wang, Xiaolei; Liu, Shaoyan; Liu, Jie (Frontiers in Endocrinology, 2021)
Objective Distant metastasis in papillary thyroid microcarcinoma (PTMC) is rare but fatal, and its relationship with patient age remains unclear. The objective of this study was to examine the association between age at diagnosis and metachronous distant metastasis in PTMC. Methods Consecutive patients who underwent thyroidectomy for PTC measuring 10 mm or less at a tertiary hospital from January 2000 to December 2016 were enrolled. Patients who had evidence of distant metastasis at diagnosis or underwent postoperative radioiodine (RAI) ablation were excluded. A Cox proportional hazards model with restricted cubic splines (RCS) was applied to examine the association between age at diagnosis and distant metastasis. Results A total of 4,749 patients were evaluated. The median age was 44 years (range, 8–78 years), and 3,700 (78%) were female. After a median follow-up of 65 months, 21 distant metastases (20 lung, 1 liver) were recognized. A univariate Cox proportional model using a 5-knot RCS revealed a significant overall (p = 0.01) and a potential nonlinear association (p = 0.08) between distant metastasis and age at diagnosis. In multivariate analysis, age at diagnosis, extrathyroidal extension (ETE), and lymph node metastasis (pN+) were independent risk factors for distant metastasis. Compared with the middle-aged group (30–45 years old), younger and older patients had a higher risk of distant metastasis [HR, 95% CI, p-value, age ≤ 30, 4.54 (0.91–22.60), 0.06, age > 45, 6.36 (1.83–22.13), <0.01]. Conclusion Age at diagnosis is associated with metachronous distant metastasis of PTMC, and patients with younger or older age have a higher risk of distant metastasis than middle-aged patients.